Ischemic stroke: clinical pathway impact. Issue 3 (15th April 2019) - de Belvis, Antonio Giulio; Lohmeyer, Franziska Michaela; Barbara, Andrea; Giubbini, Gabriele; Angioletti, Carmen; Frisullo, Giovanni; Ricciardi, Walter; Specchia, Maria Lucia
Abstract : Purpose: A clinical pathway for patients with acute ischemic stroke was implemented in 2014 by one Italian teaching hospital multidisciplinary team. The purpose of this paper is to determine whether this clinical pathway had a positive effect on patient management by comparing performance data. Design/methodology/approach: Volume, process and outcome indicators were analyzed in a pre-post retrospective observational study. Patients' (admitted in 2013 and 2015) medical records with International Classification of Diseases, ICD-9 code 433.x (precerebral artery occlusion and stenosis), 434.x (cerebral artery occlusion) and 435.x (transient cerebral ischemia) and registered correctly according to hospital guidelines were included. Findings: An increase context-sensitive in-patient numbers with more severe cerebrovascular events and an increase in patient transfers from the Stroke to Neurology Unit within three days (70 percent, p =0.25) were noted. Clinical pathway implementation led to an increase in patient flow from the Emergency Department to dedicated specialized wards such as the Stroke and Neurology Unit (23.7 percent, p <0.001). Results revealed no statistically significant decrease in readmission rates within 30 days (5.7 percent, p =0.85) and no statistically significant differences in 30-day mortality. Research limitations/implications: The pre-post retrospective observational study design was considered suitable to evaluate likely changes in patient flow after clinical pathway implementation, even though this design comes with limitations, describing only associations between exposure and outcome. Originality/value: Clinical pathway implementation showed an overall positive effect on patient management and service efficiency owing to the standardized application in time-dependent protocols and multidisciplinary/integrated care implementation, which improved all phases in acute ischemic stroke care.